Comparisons of Energetic Electron Observations Between FIREBIRD‐II CubeSats and POES/MetOp Satellites From 2018 to 2020 - I. M. Householder; K. A. Duderstadt; J. M. Pettit; A. T. Johnson; C.‐L. Huang; A. B. Crew; D. M. Klumpar; T. Raeder; J. G. Sample; M. Shumko; S. S. Smith; H. E. Spence (Space Weather)
Abstract Precipitation into the atmosphere is one of the main processes by which high energy electrons trapped in Earth's inner magnetosphere are lost from the system. Precipitating electrons can affect the chemical composition of the atmosphere and provide insight into the complex dynamics of the Van Allen radiation belts. This study compares energetic electron precipitation measurements at low‐Earth‐orbit by the Focused Investigations of Relativistic Electron Burst Intensity, Range, and Dynamics (FIREBIRD‐II) CubeSats with NOAA Polar‐orbiting Operational Environmental Satellite (POES) and ESA Meteorological Operational satellite (MetOp) satellites, which are equipped with the Medium‐Energy Proton Electron Detector (MEPED). The analysis considers 51 high quality conjunction events at >300 keV during times of low to moderate geomagnetic activity. The spacecraft capture similar electron flux variability, and FIREBIRD‐II observations fall between POES/MetOp 0° and 90° telescopes, likely a result of FIREBIRD‐II sampling both precipitating and mirrored electrons due to uncertainties in pointing direction. Results demonstrate the value of high‐resolution differential energy observations of electron precipitation by low‐cost CubeSats such as FIREBIRD‐II, especially during periods of low flux.